2017
DOI: 10.1080/07347332.2017.1329767
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and challenges for communicating the diagnosis of cancer in cross-cultural clinical settings—Perspectives from South African healthcare professionals

Abstract: Communicating the diagnosis of cancer in cross-cultural clinical settings is a complex task. This qualitative research article describes the content and process of informing Zulu patients in South Africa of the diagnosis of cancer, using osteosarcoma as the index diagnosis. We used a descriptive research design with census sampling and focus group interviews. We used an iterative thematic data analysis process and Guba's model of trustworthiness to ensure scientific rigor. Our results reinforced the use of wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The isiZulu word for cancer, umdlavuza, means something that destroys everything or something that cannot be stopped. 25 Participants further indicated that Zulu patients never asked about prognosis or the odds of surviving. This is in contrast to Western research which showed that most cancer patients wanted some degree of prognostic awareness, 6 with metastatic cancer patients wanting detailed prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…The isiZulu word for cancer, umdlavuza, means something that destroys everything or something that cannot be stopped. 25 Participants further indicated that Zulu patients never asked about prognosis or the odds of surviving. This is in contrast to Western research which showed that most cancer patients wanted some degree of prognostic awareness, 6 with metastatic cancer patients wanting detailed prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in South Africa showed that within the African cultural context, most patients viewed the definite diagnosis as having been bewitched, associated it with poor prognosis, and barely understood their diagnosis. On the other hand, health workers expressed concern of inadequate training and lack of competence in communicating diagnosis [ 77 ]. In rural Cameroon, most patients tend to disagree with the diagnosis, depending on how well they understood explanations given by the provider.…”
Section: Epidemiology In Transitionmentioning
confidence: 99%
“… 19 Healthcare professionals have reported a desire for guidelines 5 and practical instructions to guide their communication for sharing a diagnosis of cancer with patients in South Africa. 20 Specific strategies for communicating the diagnosis of osteosarcoma to Zulu patients 20 and a practice-based framework for paediatric HIV disclosure in Kenya have been published. 19 However, in some low-resource settings such as in areas of Uganda, standardised and culturally appropriate communication guidelines are limited 21 and are specific to certain diseases, for example, HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Standardised guidelines for healthcare professionals could help support successful illness-disclosure in families 19. Healthcare professionals have reported a desire for guidelines5 and practical instructions to guide their communication for sharing a diagnosis of cancer with patients in South Africa 20. Specific strategies for communicating the diagnosis of osteosarcoma to Zulu patients20 and a practice-based framework for paediatric HIV disclosure in Kenya have been published 19.…”
Section: Introductionmentioning
confidence: 99%